1992
DOI: 10.1093/njaf/9.2.58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tree Shelters on Northern Red Oak Seedlings Planted in Harvested Forest Openings

Abstract: Planting has been considered to be one solution to the problem of inadequate natural oak regeneration following harvesting in the Central Hardwood Region. Two types of tree shelters were used in two separate 3-year studies to determine their effects on the growth and survival of northern red oak seedlings planted in recently harvested forest openings, and to characterize shelter influence on microenvironmental factors. Sheltered seedlings planted in both trials exhibited significantly greater 3-year height gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…As with other oak species (e.g., Minter et al 1992; Mayhead & Boothman 1997; Sharpe et al 1999; Quilhó et al 2003), Oregon white oak responded to solid‐walled tree shelters with greater height growth but no difference in basal area growth relative to no shelter or mesh shelters. Furthermore, the effect on height growth increased over time in all the shelter trials, except the VS trial.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As with other oak species (e.g., Minter et al 1992; Mayhead & Boothman 1997; Sharpe et al 1999; Quilhó et al 2003), Oregon white oak responded to solid‐walled tree shelters with greater height growth but no difference in basal area growth relative to no shelter or mesh shelters. Furthermore, the effect on height growth increased over time in all the shelter trials, except the VS trial.…”
Section: Discussionmentioning
confidence: 66%
“…A variety of post‐planting treatments including tree shelters, mulching, fertilization, and irrigation have been tested on oak species other than Oregon white oak. Solid‐walled tree shelters reduce animal damage to oak seedlings, create a warmer, more humid microclimate (Potter 1988; Burger et al 1992; Peterson et al 1995), and have increased growth rates of many oak species (Tuley 1985; Minter et al 1992; West et al 1999; Dubois et al 2000; Taylor & Golden 2002). Mulching around planted seedlings limits growth of vegetative competition through physical impedance and light reduction (Teasdale & Mohler 2000) and may increase soil water availability (McDonald & Helgerson 1990; Truax & Gagnon 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This increase in height growth is due to improved micro-environments with in the shelters (Lantange, et al, 1990;Zastrow and Marty, 1991). Minter, et al, (1992) found that micro-environments with in shelters had increased levels of CO2 and relative hiunidity, which reduced plant transpiration losses.…”
Section: Growth Mortality and Stockingmentioning
confidence: 96%
“…The British findings have prompted further research on the application and effects of tree shelters in the United States. Lantagne, et al (1990), Zastrow and Marty (1991), and Minter, et al (1992) have studied the effect of tree shelters on Quercus rubra seedlings planted in harvested forest openings. Lantange, et al (1990) concluded that tree shelters used in a Michigan clearcut promoted height growth by improving micro-environments of Quercus rubra seedlings and reallocating growth fi-om branches and stem diameter to shoot elongation for sheltered seedlings.…”
Section: Tree Sheltersmentioning
confidence: 99%
See 1 more Smart Citation